Neuroprotective Ability of Tobacco Stem Silver Nanoparticle on Rat PC-12 Cells - Sharma, Yash (Asian Journal of Pharmaceutics (AJP), 2017)
Aims: The present study was approached to determine the neuroprotective ability of synthesize silver nanoparticles (AgNPs) of stem of Nicotiana tabacum (TSAgNPs). Materials and Methods: Aqueous extract of tobacco stem was used as bioreducing agent to synthesize nanoparticles and was characterized by ultraviolet visible (UV-Vis) spectra scan, dynamic light scattering (DLS), and Fourier transformed infrared (FT-IR). Antioxidant content in TSAgNPs was determined by electron transfer assay (total flavonoid count, total phenolic content, and 1, 1-diphenyl-2 picrylhydrazyl (DPPH) free radical scavenging), enzymatic biochemical assay (superoxide dismutase [SOD], catalase [CAT], and glutathione S-transferase [GST]), and non-enzymatic biochemical assay (reduced glutathione [GSH] content and malondialdehyde [MDA] content). Neuroprotective ability was determined by observing in vitro antioxidant activity of TSAgNPs on Rat PC-12 cells by exposing it to hydrogen peroxide as neurotoxic agent. Statistical Analysis Used: To estimate the accuracy of the experimental data, each experiment was performed in triplicates, and the result was expressed as the mean ± standard deviation of three replications. P < 0.05 was considered as statistically significant. Results: This was found from this study that by UV-Vis spectra scan has shown the maximum absorbance at 456 nm, whereas DLS has shown the size of TSAgNPs, i.e., 565.1 Dia(nm). FT-IR has confirmed the bioconjugate formation by giving intense bands at 3298.83, 2333.38, 1639.39, 1085.46, and 1038.83/cm wavenumber. Antioxidant content in TSAgNPs was found to be present, and it has shown the presence of flavonoid content, i.e., 74.85 ± 0.22 mg QE/g of TSAgNPs, phenolic content, i.e., 502 ± 0.06 mg QE/g of TSAgNPs and DPPH free radical scavenging found to be 60% of inhibition. Enzymatic and non-enzymatic biochemical assay was determined and has shown the presence of maximum specific enzyme activity in TSAgNPs. In vitro antioxidant activity, i.e., SOD, CAT, GST, GSH content, and MDA content in Rat PC-12 cells was found to be maximum as the volume of TSAgNPs increased in cells against the neurotoxic agent, and this observation reveals the presence of neuroprotective ability. Conclusions: This can be concluded from the present study that TSAgNPs can be used as a natural herbal remedy to treat the neurological disorders as a neuroprotective agent and to make use of waste material, i.e., stem of tobacco for therapeutic purposes.